Impacts of extension access and cooperative membership on technology adoption and household welfare - Assfaw Wossen, Tesfamicheal; Abdoulaye, Tahirou; Alene, A.; Haile, M.G.; Feleke, S.; Olanrewaju, A.S.; Manyong, Victor M. (Elsevier, 2017)
This paper examines the impacts of access to extension services and cooperative membership on technology adoption, asset ownership and poverty using household-level data from rural Nigeria. Using different matching techniques and endogenous switching regression approach, we find that both extension access and cooperative membership have a positive and statistically significant effect on technology adoption and household welfare. Moreover, we find that both extension access and cooperative membership have heterogeneous impacts. In particular, we find evidence of a positive selection as the average treatment effects of extension access and cooperative membership are higher for farmers with the highest propensity to access extension and cooperative services. The impact of extension services on poverty reduction and of cooperatives on technology adoption is significantly stronger for smallholders with access to formal credit than for those without access. This implies that expanding rural financial markets can maximize the potential positive impacts of extension and cooperative services on farmers’ productivity and welfare.